PVA-Coumarin Films: Materials for Optical Applications - Mohamed, N.; Badr, Y. A.; El-Kader, K. M. Abd (Journal of Composites and Biodegradable Polymers, 2015)
Pure Poly(vinylacohol) (PVA) and PVA-coum films with different concentrations were prepared by a casting technique. Optical absorption and mechanical properties were measured. The UV–Vis absorption spectra gave the same band positions but the absorption intensity increases with increasing coumarin concentration. The dependence of the absorption coefficient on the photon energy has been determined and the energy gaps and band tails were calculated. The topography of the surface was measured by atomic force microscope (AFM). It was found that Young’s modulus, the strength at the break and the band tail increase while the optical gaps for PVA-coum films decrease. RMS roughness of the surface for prepared films decreases as the coumarin concentration is increased. The obtained results illustrated that this material has promising applications in optical industries.